<htm> Desenvolvimento agrícola e produção pesqueira no Brasil no período 1992-2011 </htm> - Chaves, Paulo de Tarso da Cunha (Acta Biológica Paranaense, 2017)
<htm> Desenvolvimento agrícola e produção pesqueira no Brasil no período 1992-2011 </htm>